Hermeneutical analysis of the concept of body in Bachelor of Physical Education students and Sports from the University of Los Llanos (Impetus, 2021)
The result of this scientific article is the product of the implementation or realization of an objective of the project macro identities in transit: communication, body and technology in urban youth of Villavicencio led by the research group "body and motor game" at the head of the principal investigator Héctor Rolando Chaparro Hurtado. The inclusion of a subject to the physical education and sports degree program at the University of Los Llanos implies familiarizing him with the importance of this discipline in society. Familiarizing it sounds and means superfluous, however it is mentioned in this way since physical education has been taken as a third grade or filler (school) subject, in the same way, this is seen by some students: “an easy career and simplistic". Due to the diversity and fields in which physical education can be performed, it is important to inquire about the meaning (concept) of the body.